The Effects of Endurance Exercise in Hypoxia on Acid-Base Balance, Potassium Kinetics, and Exogenous Glucose Oxidation - Sumi, Daichi; Kasai, Nobukazu; Ito, Hiroto; Goto, Kazushige (Frontiers in Physiology, 2019)
PURPOSE: To investigate the carbohydrate metabolism, acid–base balance, and potassium kinetics in response to exercise in moderate hypoxia among endurance athletes. METHODS: Nine trained endurance athletes [maximal oxygen uptake (VO2max): 62.5 ± 1.2 mL/kg/min] completed two different trials on different days: either exercise in moderate hypoxia [fraction of inspired oxygen (FiO2) = 14.5%, HYPO] or exercise in normoxia (FiO2 = 20.9%, NOR). They performed a high-intensity interval-type endurance exercise consisting of 10 × 3 min runs at 90% of VO2max with 60 s of running (active rest) at 50% of VO2max between sets in hypoxia (HYPO) or normoxia (NOR). Venous blood samples were obtained before exercise and during the post-exercise. The subjects consumed 13C-labeled glucose immediately before exercise, and we collected expired gas samples during exercise to determine the 13C-excretion (calculated as 13CO2/12CO2). RESULTS: The running velocities were significantly lower in HYPO (15.0 ± 0.2 km/h) than in NOR (16.4 ± 0.3 km/h, P < 0.0001). Despite the lower running velocity, we found a significantly greater exercise-induced blood lactate elevation in HYPO compared with in NOR (P = 0.002). The bicarbonate ion concentration (P = 0.002) and blood pH (P = 0.002) were significantly lower in HYPO than in NOR. There were no significant differences between the two trials regarding the exercise-induced blood potassium elevation (P = 0.87) or 13C-excretion (HYPO, 0.21 ± 0.02 mmol･39-min; NOR, 0.14 ± 0.03 mmol･39-min; P = 0.10). CONCLUSION: Endurance exercise in moderate hypoxia elicited a decline in blood pH. However, it did not augment the exercise-induced blood K+ elevation or exogenous glucose oxidation (13C-excretion) compared with the equivalent exercise in normoxia among endurance athletes. The findings suggest that endurance exercise in moderate hypoxia causes greater metabolic stress and similar exercise-induced elevation of blood K+ and exogenous glucose oxidation compared with the same exercise in normoxia, despite lower mechanical stress (i.e., lower running velocity).